The incidence of smoking and risk factors for smoking initiation in medical faculty students: cohort study - Turkay Mehtap; Donmez Levent; Senol Yesim; Aktekin Mehmet (BMC, 2006)
Abstract Background Medical education requires detailed investigation because it is a period during which the attitudes and behaviors of physicians develop. The purpose of this study was to calculate the yearly smoking prevalence and incidence rates of medical faculty students and to identify the risk factors for adopting smoking behaviour. Methods This is a cohort study in which every student was asked about their smoking habits at the time of first registration to the medical faculty, and was monitored every year. Smoking prevalence, yearly incidence of initiation of smoking and average years of smoking were calculated in analysis. Results At the time of registration, 21.8% of the students smoked. At the end of six years, males had smoked for an average of 2.6 ± 3.0 years and females for 1.0 ± 1.8 years (p < 0.05). Of the 93 medical students who were not smokers at the time of registration, 30 (32.3%) were smokers at the end of the 6 years of the course. Conclusion The first 3 years of medical education are the most risky period for initiation of smoking. We found that factors such as being male, having a smoking friend in the same environment and having a high trait anxiety score were related to the initiation of smoking. Targeted smoking training should be mandatory for students in the Medical Faculty.